Desempenho de trigo sob doses de nitrogênio em sucessão ao trigo-mourisco como planta de cobertura - Mitrut, Rian Augusto (2025)
This study aimed to evaluate the performance of wheat (Triticum aestivum L.) under nitrogen rates in succession to buckwheat (Fagopyrum esculentum Moench) as a cover crop. Wheat was grown on buckwheat straw in a randomized block design with four treatments and four replicates. The treatments consisted of the application of N rates (0, 60, 90 and 120 kg ha−1) as topdressing (tillering), using urea as the source. The production of dry matter mass and nutrient absorption by buckwheat were evaluated. Subsequently, the N, P and K contents in the wheat flag leaf were evaluated, in addition to plant height, number of spikes per square meter, number of grains per spike, thousand-grain weight and wheat grain yield. Wheat grain yield showed an increasing linear response to N application, ranging from 2324 to 4097 kg ha−1. Thus, although buckwheat contributed to nutrient cycling, its straw was not sufficient to fully meet the wheat’s nitrogen demand, making supplementary fertilization necessary to maximize productivity.